2004
DOI: 10.4040/jkan.2004.34.5.859
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of the Experience of Preceptors in Clinical Education for Senior Student Nurses

Abstract: This study suggests that interventions for encouragement and socialization of preceptors should be developed to promote clinical education for senior student nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Previous studies have suggested that health organizations must train preceptors to effectively interact with newly graduated nurses to reduce turnover intention [10][11][12]. However, in some cases, they became a preceptor without receiving structured preceptor training or preparing themselves for the role, which also resulted in excessive work and stress [13,14]. A study conducted in Taiwan and the U.K. found that most nurses became preceptors without receiving sufficient training, and that the training they received was mostly theoretical rather than practical.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that health organizations must train preceptors to effectively interact with newly graduated nurses to reduce turnover intention [10][11][12]. However, in some cases, they became a preceptor without receiving structured preceptor training or preparing themselves for the role, which also resulted in excessive work and stress [13,14]. A study conducted in Taiwan and the U.K. found that most nurses became preceptors without receiving sufficient training, and that the training they received was mostly theoretical rather than practical.…”
Section: Introductionmentioning
confidence: 99%
“…5977/jkasne.2014.20.3.443 간호대학 임상실습강사의 역할 경험 그러나 간호 분야에서 실습지도자에 대한 연구는 임상 현 장에 근무하는 수간호사나 간호사를 대상으로 한 연구 (Son, Kim, Lee, Jun, & Han, 1998), 간호사를 활용한 학생 실습 프 리셉터에 대한 연구 (Kim, Kim, & Park, 2012;Hur et al, 2004), 간호대학 교수의 임상실습 지도 경험에 대한 연구 (Song, Kim, & Kim, 2010 …”
unclassified